Chemical deactivation of Selective Catalytic Reduction catalyst: Investigating the influence and mechanism of SeO2 poisoning. (1st June 2020) - Xu, Liwen; Wu, Qingru; Chang, Huazhen; Li, Guoliang; Zou, Jing; Wang, Shuxiao
Graphical abstract: Highlights: Se concentration at the SCR inlets is high, mostly in the gaseous phase. Se is one of the major contributors to chemical poisoning on SCR catalysts. Formed Se 4+ species prohibit NH3 adsorption and oxidize NH3 into N2 O. Abstract: Selenium (Se) is a major trace element in coal that can easily volatize and become part of flue gas during the combustion process. Currently, the interactions between SeO2 and Selective Catalytic Reduction (SCR) catalysts remain unclear. In this study, a field test at four coal-fired power plants found that the Se concentration at the SCR inlets were relatively high, with more than 95% present in its gaseous phase. To explore possible interactions between SeO2 and SCR catalyst, a V2 O5 -WO3 /TiO2 (VWTi) catalyst was subjected to various degrees of in situ SeO2 poisoning. A positive correlation between the decreases in catalytic activity and N2 selectivity and an increasing amount of SeO2 deposition was observed. The decreases in NH3 -adsorption capacity and strong acid sites activation ability were responsible for the loss in catalytic activity, while higher ratio of chemisorbed oxygen and stronger reducibility resulted in NH3 being oxidized to N2 O and N2 selectivity loss. Based on these results, it is clear that SeO2 poisoning of SCR catalysts should be taken into consideration to ensure the reliable operation of SCR systems.